1999
DOI: 10.1046/j.1442-2042.1999.06338.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of ejaculation in the treatment of chronic non‐bacterial prostatitis

Abstract: Background: Chronic non-bacterial prostatitis (NBP) is the most common prostatitis syndrome. Prevention and cure are not possible because the cause of NBP is unknown. However, patients may benefit from supportive measures. The impact of the frequency of ejaculation alone on the course of NBP was evaluated in the present study. Methods: Thirty-four single male patients who avoided masturbation and extramarital sexual intercourse for personal and/or religious beliefs and who did not respond to a clinical trial o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…Although the concept of sex is often associated with long-lasting romantic relationships, sexual experiences can manifest themselves in different ways. Studies have demonstrated that, for men, there are different positive psychological and physiological effects of sexual experiences, caused, for instance, by masturbation (e.g., [12]) or by sexual intercourse in short-term relationships (e.g., [13]). Despite the lack of consensus regarding whether sex drive is based on psychological or physiological processes or an integrated process, every human experiences sexual tension [14][15][16].…”
Section: Sex and Attractionmentioning
confidence: 99%
“…Although the concept of sex is often associated with long-lasting romantic relationships, sexual experiences can manifest themselves in different ways. Studies have demonstrated that, for men, there are different positive psychological and physiological effects of sexual experiences, caused, for instance, by masturbation (e.g., [12]) or by sexual intercourse in short-term relationships (e.g., [13]). Despite the lack of consensus regarding whether sex drive is based on psychological or physiological processes or an integrated process, every human experiences sexual tension [14][15][16].…”
Section: Sex and Attractionmentioning
confidence: 99%
“…10,11 Sex advice books for lay readers now generally regard masturbation not just neutrally but positively. 12,13 Few of the national sex surveys in other countries collected data about masturbation.…”
Section: Diversity Of Experiencementioning
confidence: 99%
“…Efficacy has not been established in clinical trials. Although many men have exacerbation of symptoms with ejaculation [15], others have a reduction in symptoms with regular ejaculation [16]. Ullrich et al [17•] conducted a study to examine whether perceived stress was associated longitudinally with pain intensity and pain-related disability in a sample of men (n = 224) with nonbacterial prostatitis/ pelvic pain.…”
Section: Supportive Measuresmentioning
confidence: 99%